Pengaruh Digital Marketing dan Word of Mouth Terhadap Keputusan Berkunjung (Studi pada Pabrik Susu Berastagi): Penelitian - Virgin Threisia Br Bangun; Nana Dyki Dirbawanto; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Tourists’ decisions to visit a destination play an important role in the growth of the tourism industry. In recent years, nature-based tourism has become increasingly popular as a preferred option for leisure. This study examines the influence of digital marketing and word of mouth on tourists’ decisions to visit the Berastagi Milk Factory tourist attraction. The research adopts a quantitative associative approach with purposive sampling of visitors as respondents. Data were collected through questionnaires as primary data and literature studies as secondary data. The analytical methods include validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results indicate that both digital marketing and word of mouth have a significant partial effect on visiting decisions. Simultaneously, these two variables significantly influence tourist decisions in choosing a destination. The correlation analysis shows a very strong relationship between the two independent variables and visiting decisions, with an R value of 0.811. Furthermore, the adjusted R-square value reveals that 65.1% of the variation in visiting decisions can be explained by digital marketing and word of mouth, while the remaining 34.9% is influenced by other factors not examined in this study. These findings highlight the importance of utilizing digital marketing strategies and encouraging positive word of mouth to increase tourist visits.